2016
DOI: 10.3126/njog.v10i2.14331
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Tumors of the Female Genital Tract – a Hospital Based Analysis

Abstract: were included in the study.Results: Among 62 cases, cervical cancer was the commonest (71%) followed by ovarian cancer (14%), endometrial FDQFHU DQG FKRULRFDUFLQRPD 0DMRULW\ RI ZRPHQ EHORQJHG WR \HDUV IRU HDFK W\SH RI WXPRUV )RXU¿IWK RI endometrial, half of the cervical and one-third of ovarian cancers were among grand-multipara. Sixty nine percent of women received treatment with 22 (9 cervical, 9 ovarian, 3 endometrial and one of corpus uteri) surgical and 21 primary chemo/ radiotherapy but 19 (31%) were los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
(9 reference statements)
2
4
0
Order By: Relevance
“…Endometrial cancer remained the third common gynecological malignancy in our study (9.23%) which is similar to Pokhrel et al 10 (10%) but slightly higher than Jha et al 9 (5.5%), Dhakal et al 11 (2.1%) which is in contrast to the findings of western countries where endometrial cancer is 35% of all gynecological malignancies. The low incidence of endometrial cancer may be due to the low incidence of obesity, hypertension, diabetes mellitus, and breast cancer in our country as compared to the west.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Endometrial cancer remained the third common gynecological malignancy in our study (9.23%) which is similar to Pokhrel et al 10 (10%) but slightly higher than Jha et al 9 (5.5%), Dhakal et al 11 (2.1%) which is in contrast to the findings of western countries where endometrial cancer is 35% of all gynecological malignancies. The low incidence of endometrial cancer may be due to the low incidence of obesity, hypertension, diabetes mellitus, and breast cancer in our country as compared to the west.…”
Section: Discussionsupporting
confidence: 87%
“…11,17 Endometroid adenocarcinoma variety was the commonest endometrial cancer in our study which is correlating with findings in another study. 9 Thus serous adenocarcinoma is the most common ovarian cancer, non-keratinizing squamous cell cancer is the most common cervical cancer and endometroid adenocarcinoma is the most common endometrial carcinoma in the present study.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In our study majority of the women with endometrial cancer were in the age group of 61-70 years similar to the study of Gaikwad SL et al [12] who also reported incidence of endometrial carcinoma in 6th and 7 th decade. The mean age of endometrial cancer ranged from 52 to 57 in other studies [17,26] The percentage of carcinoma endometrium in our study constituted 4.82% cases of the total neoplastic lesions. In the study conducted by Gaikwad SL et al [12] and Khandekar S et al [15] only 2.14% and 3.38% of endometrial carcinomas respectively, were reported which is lower as compared to our study.…”
Section: Discussionmentioning
confidence: 39%